Conducting fit‐for‐purpose food safety risk assessments. (8th July 2019) - Devos, Yann; Elliott, Kevin C; Macdonald, Philip; McComas, Katherine; Parrino, Lucia; Vrbos, Domagoj; Robinson, Tobin; Spiegelhalter, David; Gallani, Barbara
Abstract: The interplay between science, risk assessment and risk management has always been complex, and even more so in a world increasingly characterised by rapid technical innovation, new modes of communication, suspicion about authorities and experts, and demands for people to have a say in decisions that are made on their behalf. In this challenging era where scientific advice on food safety has never been in greater demand, risk managers should effectively navigate the interplay between facts and values and be able to rely on robust and fit‐for‐purpose risk assessments to aid them. The fact that societal resistance is often encountered when scientific advice on food safety operates at a distance from social values and fails to actively engage with citizens, has led to increasing emphasis on the need to advance forms of risk assessment that are more contextual, and socially sound and accountable. EFSA's third Scientific Conference explored how risk assessments could be constructed to most usefully meet society's needs and thus connect science with society, while remaining scientifically robust. Contributors to the conference highlighted the need to: (1) frame risk assessments by clear policy goals and decision‐making criteria; (2) begin risk assessments with an explicit problem formulation to identify relevant information; (3) make use of reliable risk assessment studies; (4) be explicit about value judgements; (5) address and communicate scientific uncertainty; (6) follow trustworthy processes; (7) publish the evidence and data, and report the way in which they are used in a transparent manner; (8) ensure effective communication throughout the risk analysis process; (9) involve society, as appropriate; and (10) weigh risks and benefits on request. Implementation of these recommendations would contribute to increased credibility and trustworthiness of food safety risk assessments.